Guest Editors - Extended Abstracts - The 23rd Himalayan-Karakoram-Tibet Workshop - Editor, The (Himalayan Journal of Sciences, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> NOTICE This is a special issue of the Himalayan Journal of Sciences, containing extended abstracts of papers to be presented at the 23rd Himalaya-Karakoram-Tibet Workshop to be held in Leh, Ladakh, India August 08-11, 2008. The issue was produced by guest editors and its contents have not been subjected to peer review.